The Influence of Principal Leadership and Teacher Competence on Teacher Performance Through Job Satisfaction at State Senior High School 5 Pekanbaru - Xavier, Mu’afa Khairy; Fitri, Kurniawaty; Tarigan, Mida Aprilina (CV. Rayyan Dwi Bharata, 2025)
This research was conducted with purpose to determine the effect of principal leadership and competence on teacher performance through job satisfaction at SMAN 5 Pekanbaru. The population in this study were all civil servant teachers at SMAN 5 Pekanbaru. The number of samples in this study was carried out by means of saturated sampling technique (census), namely making all members of the population into samples, so that the number of samples in this study was members of the population into a sample, so that the number of samples in this study was 55 teachers. The data analysis method of this research uses analysis method Structural Equation Modelling - Partial Least Square (SEM-PLS) with SmartPLS software version 4.1.1.3. The results showed that principal leadership has a positive and significant effect on teacher performance. Competence has a positive and significant effect on teacher performance. Principal Leadership has a positive and significant effect on job satisfaction. Competence has a positive and significant effect on job satisfaction. Job Satisfaction has a positive and significant effect on teacher performance. Principal Leadership has a positive and significant effect on teacher performance through job satisfaction. Competence has a positive and significant effect on teacher performance through job satisfaction.